1987
DOI: 10.1007/bf00117863
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity, sister chromatid exchange inducibility andin vitro cell transforming ability of particulates from Athens air

Abstract: Airborne particulates were collected over a period of twelve months by the use of Hi-Vol samplers in the basin of Athens, Greece. N-Hexane extracts were tested in a battery of in vitro tests for their ability to induce mutation in bacteria as well as mutation, sister chromatid exchange and morphological transformation in cultured mammalian cells. Positive results were found for mutagenicity with Salmonella strain TA98 in the Ames assay, for sister chromatid exchange induction in CHO cells and for transformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

1990
1990
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
5
0
2
Order By: Relevance
“…DEPs are heterogeneous, consisting of more than 450 different organic compounds, including xenobiotics such as PAHs, halogenated aromatic hydrocarbons, and redox-active quinones (Athanasiou et al 1987; Li et al 2002; Whong et al 1981). Some of the individual components are cytotoxic and mutagenic in mammalian cells, but most are promutagens that require activation to electrophilic metabolites to exert their mutagenic or carcinogenic effects (Xue and Warshawsky 2005).…”
Section: Discussionmentioning
confidence: 99%
“…DEPs are heterogeneous, consisting of more than 450 different organic compounds, including xenobiotics such as PAHs, halogenated aromatic hydrocarbons, and redox-active quinones (Athanasiou et al 1987; Li et al 2002; Whong et al 1981). Some of the individual components are cytotoxic and mutagenic in mammalian cells, but most are promutagens that require activation to electrophilic metabolites to exert their mutagenic or carcinogenic effects (Xue and Warshawsky 2005).…”
Section: Discussionmentioning
confidence: 99%
“…We have been using the BALB/c 3T3 cell transformation system in studies of the transforming potency of some genotoxic and nongenotoxic carcinogens and environmental pollutants [8,41] and have also adapted the protocol for detection of tumor promoters. The conceptual advantage of this assay is that transformed foci emerge from a confluent lawn of nontransformed cells; this therefore simulates in vivo promotion more closely than say the clonal SHE cell assay.…”
Section: Enhancement Of Cell Transformationmentioning
confidence: 99%
“…The results of mutagenicity testing of air samples collected before the war indicated that, in general, the level of air pollution by potentially carcinogenic agents was relatively low in Saudi Arabian cities compared to the data obtained with urban air of major industrial countries (Tokiwa et al 1977, Athanasiou et al 1987). However, there was a clear indication that the histidine revertants/m 3 of air varied considerably with air samples from different areas of Saudi Arabia depending on the presence or absence of industrial sites, oil refineries, automobile traffic and construction activities.…”
Section: Discussionmentioning
confidence: 93%
“…Air-borne toxic agents are produced by industrial and automobile emissions as well as by burning of various organic substances (Suess et al, 1985). As the potential carcinogenic effects of air pollutants are of major concern, attempts have been made to determine and monitor genotoxic properties of air particulates in various cities of the industrialized countries (Sutou et al, 1980, Athanasiou et al, Downloaded by [New York University] at 10:21 05 November 20141986, 1987, Crebelli et al, 1988, Hoyer et al, 1992, Nardini and Clonfero 1992, Nardini et al, 1994. These studies have demonstrated the usefulness of Ames' histidine reversion assay in suitable tester strains of Salmonella typhimurium for screening organic extracts of air samples showing mutagenic activity.…”
Section: Introductionmentioning
confidence: 99%